The intervention of maternal nutrition literacy has the potential to prevent childhood stunting: Randomized control trials - Sirajuddin Sirajuddin; Saifuddin Sirajuddin; Amran Razak; Ansariadi Ansariadi; Ridwan M Thaha; Toto Sudargo (SAGE Publishing, 2021)
Background: Stunting is the impaired growth and development of children due to poor nutrition, repeated infection, and inadequate psychological stimulation. This research aims to examine the impact of maternal nutrition literacy (MNL) in increasing the height or score of a stunted child. Design and Methods: This study is a randomized control trial, which uses a sample size of 85 participants, 43 interventions and 42 controls, an 80% stress test and a 95% confidence level. The intervention group of the MNL consists of families with children under the age of five, focused on the mother's ability to perform breastfeeding, hygiene activities, care, and intervention for 3 months. Result: The status of stunting was determined by the different distribution of stunting before and after the intervention in both the intervention and control groups. There was a decrease of about 9.3% of MNL in the intervention group, while in the control group it decreased by just 2.4% (p<0.05). Conclusions: It can be concluded that MNL has an effect in preventing stunting, and it is recommended that preventive measures should focus more on normal children, while stunted children should be provided with breastfeeding as the core of MNL.